ARTIFICIAL INTELLIGENCE AND THE TECHNOCRATIC PARADIGM: AN INDIAN PERSPECTIVE - Stanley, SJ, Sahayaraj (Asian Horizons, 2020)
We live in turbulent times. Using the tools of technology, humanity slowly surges ahead. Scientific advancements have obviously made our lives better, cosier and trouble-free. The technological progress, which is presented as a paradigm, lies in the hands of the privileged few. Pope Francis, who uses this term ‘technocratic paradigm’ points out that due to this orientation, the human person as the creator and simulator, tends to do more harm than good. The Digital India programme by the government fails to take into account the millions of poor who do not get detected by the technical radar. The victims of this paradigm are the poor and the vulnerable of the society, who are also rightful inhabitants of this planet earth. The Human person, who is a thinking animal, needs to think intelligently towards the wellbeing of the entire society. Technology needs to be pro-poor, pro-planet and prosperity sans fraudulent profit. If unchecked, losing its ethical soul and neutrality, the technological progress will create maximum mayhem and moral madness.